Southwest monsoon influences the water quality and waste assimilative capacity in the Mandovi estuary (Goa state, India) - Vishnuradhan, Renjith; Sagayadoss, Jerome; Seelan, Ebin; Vethamony, Ponnumony; Shirodkar, Prabhakar; Zainudin, Zaki; Shirodkar, Supriya (Taylor & Francis, 2014)
The monsoon-dominated Mandovi estuary is located in Goa state – a global tourist destination along the centralwest coast of India. In addition to factor analyses of water quality data, the water quality index (WQI), trophic state index (TSI) and percentage of freshwater volume in the estuary are calculated in order to infer the general waste assimilative capacity and prevailing water quality conditions. Factor anal- ysis showed a dominance of PO4–P, NO2–N, NH3–N, total suspended solids (TSS) and turbidity during southwest (SW) monsoon relative to other seasons. The WQI suggested that an increase in nutrients, turbidity and TSS during SW monsoon increase the WQI values beyond 2, rendering the water at some locations slightly polluted. During pre-monsoon, considerable increase in the WQI is observed at all the upstream stations rendering slightly polluted water at these stations. The TSI showed an average value of 46.95 during SW monsoon, 42.43 during post-monsoon and 48.42 during the pre-monsoon seasons, suggesting better productivity level during pre-monsoon, followed by SW monsoon, but the least dur- ing the post-monsoon. All the seasons, however, indicated a mesotrophic condition in the estuary and the assimilative capacity of the estuary is found to be in good to fairly good state (pre-monsoon < SW monsoon < post-monsoon).